(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Lower genital tract infections are common in women aged 15 to 49 years and have significant impacts on reproductive and overall health. Objective: This study aimed to identify factors related to lower genital tract infections in women aged 15 to 49 years at Tra Vinh Pediatric Hospital. Research methods: A cross-sectional survey was conducted on 340 women aged 15 to 40 years at the hospital’s outpatient clinic from April to August 2020. The research participants were directly interviewed using a structured questionnaire, and outpatient medical records were also observed. Results: Multivariable logistic regression analysis showed that women using intrauterine devices for contraception were associated with a higher risk of lower genital tract infections, with an odds ratio of 36.00 (95% CI: 1.57 - 826.12). Conclusions: Intrauterine contraceptive methods are independently associated with lower genital tract infections in women in the study. Although there is still no strong evidence about this causal relationship in the literature, healthcare professionals should consult women with reproductive health issues related to contraception and promote their vaginal hygiene practices.